Familial CD45RA– T cells to treat severe refractory infections in immunocompromised patients - Al-Akioui Sanz, Karima; Echecopar Parente, Carlos; Ferreras, Cristina; Menéndez Ribes, Marta; Navarro, Alfonso; Mestre, Carmen; Clares, Laura; Vicario, José Luis; Balas, Antonio; De Paz, Raquel; López Granados, Eduardo; Sánchez Zapardiel, Elena; et al. (Frontiers in Medicine, 2023)
Background Immunocompromised patients are susceptible to high-risk opportunistic infections and malignant diseases. Most antiviral and antifungal drugs are quite toxic, relatively ineffective, and induce resistance in the long term. The transfer of pathogen-specific Cytotoxic T-Lymphocytes has shown a minimal toxicity profile and effectiveness in treating Cytomegalovirus, Adenovirus, Epstein - Barr virus, BK Virus and Aspergillus infections, but this therapy have the main limitations of regulatory issues, high cost, and absence of public cell banks. However, CD45RA– cells containing pathogen-specific memory T-cells involve a less complex manufacturing and regulatory process and are cheaper, feasible, safe, and potentially effective. Methods We present preliminary data from six immunocompromised patients: four who had severe infectious diseases and two who had EBV lymphoproliferative disease. All of them underwent multiple safe familial CD45RA– T-cell infusions as adoptive passive cell therapy, containing Cytomegalovirus, Epstein - Barr virus, BK virus, and Aspergillus-specific memory T-cells. We also present the method for selecting the best donors for CD45RA– cells in each case and the procedure to isolate and store these cells. Results The infusions were safe, there was no case of graft-versus host disease, and they showed a clear clinical benefit. The patients treated for BK virus nephritis, Cytomegalovirus encephalitis, Cytomegalovirus reactivation, and disseminated invasive aspergillosis experienced pathogen clearance, complete resolution of symptoms in 4-6 weeks and a lymphocyte increase in 3 of 4 cases after 3–4 months. Donor T cell transient microchimerism was detected in one patient. The two patients treated for EBV lymphoproliferative disease underwent chemotherapy and several infusions of CD45RA– memory T-cells containing EBV cytotoxic lymphocytes. Donor T-cell microchimerism was observed in both patients. The viremia cleared in one of the patients, and in the other, despite the viremia not clearing, hepatic lymphoproliferative disease remained stable and was ultimately cured with EBV-specific Cytotoxic T-Lymphocytes. Conclusion The use of familial CD45RA– T-cells containing specific Cytotoxic T-lymphocytes is a feasible, safe and potential effective approach for treating severe pathogen infections in immunocompromised patients through a third party donor. Furthermore, this approach might be of universal use with fewer institutional and regulatory barriers.